Isolasi dan Identifikasi Kapang Saprofitik pada Sampel Tanah di Sekitar Kawasan Gunung Gamalama, Ternate - Muhammad Ilyas (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2010)
Microorganisms, such as mould and bacteria, have important roles in organic matter decomposition; and this process is fundamental to maintain soil structure and fertility. Moulds have hypha with filament structures that can penetrate to the substrates. Their enzymatic capability is higher than that of bacteria, especially in decomposing organic compounds like lignin and cellulose. The objective of the study was to isolate and identify saprophytic mould inhabiting soil of Mount Gamalama, Ternate, North Moluccas. The mould isolation was based on sample dillution method with Rose Bengal Cloramphenicol Agar isolation media. The abundance of saprophytic mould counted by measuring the average Colony Forming Unit (CFU)/ml of all mould colonies which grown on isolated media by Total Plate Count (TPC) method. The diversity of isolated mould was identified based on phenotypic characters by observing both macroscopic and microscopic morphology. The result showed that the average of mould colonies were between 13,30 x104 and 78,15 x104 CFU/ml. Identification based on morphology from selected mould isolates showed that 25 fungal taxa and two groups of unidentified fungal isolates were identified.